An Integrative Analysis of Product Reviews, Siddiq Values, and Prices on Repeat Orders of Skincare Products Among Gen Z Consumers in Indonesia - Rona Salsabila; Siti Masrohatin; Fauzan Fauzan (Eastasouth Institute, 2026)
The development of the skincare industry among Gen Z in Indonesia shows significant growth. Generation Z is known as a group of consumers who are critical and actively seek information before purchasing, especially regarding product authenticity and transparency of the value offered by manufacturers. This study aims to analyze the influence of product reviews, siddiq values, and prices on repeat orders of skincare products among Gen Z consumers in Indonesia, both partially and simultaneously. This research uses a quantitative approach, with a descriptive research type. Data was collected through a survey method. The population in this study is generation Z in Indonesia, because the population size in this study is not yet known. Therefore, the researcher used a nonprobability sampling technique using a purposive sampling method with the criteria, Generation Z (aged between 13 and 28 years) and using skincare products. This study took a sample of 150 sample respondents. Data analysis used multiple linear regression with SPSS 25. The results of this study stated that the product review variable had a positive and significant effect with a t-test of 3.061. The siddiq value has a positive and significant effect with a t-count of 6.238. Price has a positive and significant effect with a t-test of 3.987. The results of the simultaneous test of product reviews, siddiq values, and prices have a significant effect on repeat orders (Y).